2021
DOI: 10.3390/children8010054
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Frequency and Distinguishing Features of Sleep Disorders in Pediatric Palliative Care Incorporating a Systematic Sleep Protocol

Abstract: Currently, no concrete figures on sleep disorders and sleep characteristics in children and adolescents with life-limiting conditions (LLC) and severe neurological impairment (SNI) based on pediatric palliative care professionals’ assessment and following an official classification system such as the International Classification of Sleep Disorders (ICSD-3) exist. The ICSD-3 sleep disorders of inpatient children and adolescents with LLC and SNI (N = 70) were assessed by professionals using a recording sheet (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Gastroesophageal reflux and feeding tubes ( n = 57, 56%) was the most common topic, with subtopics of gastroesophageal reflux ( n = 7), 7,42–44,102–104 gastrostomy tube outcomes ( n = 24), 9,39,45,46,56–65,81–84,105–110 and antireflux procedures ( n = 26) 8,47–55,66–71,85,86,111–118 . Other topics included aspiration and respiratory issues ( n = 13, 13%) 72,73,87–93,119–122 ; symptoms, palliative care, and quality of life ( n = 12, 12%) 38,41,74–77,94–97,123,124 ; growth and endocrinology ( n = 10, 10%) 78,98,99,125–131 ; caregivers and care burden ( n = 7, 7%) 10,37,40,79,80,100,132 ; other ( n = 2, 2%) 101,133 ; and musculoskeletal ( n = 1, 1%) 134 . Most studies ( n = 54, 53%) were retrospective cohorts or case series (Supporting Information: eFigure ), with a median sample size of 48 patients (range 20–240).…”
Section: Resultsmentioning
confidence: 99%
“…Gastroesophageal reflux and feeding tubes ( n = 57, 56%) was the most common topic, with subtopics of gastroesophageal reflux ( n = 7), 7,42–44,102–104 gastrostomy tube outcomes ( n = 24), 9,39,45,46,56–65,81–84,105–110 and antireflux procedures ( n = 26) 8,47–55,66–71,85,86,111–118 . Other topics included aspiration and respiratory issues ( n = 13, 13%) 72,73,87–93,119–122 ; symptoms, palliative care, and quality of life ( n = 12, 12%) 38,41,74–77,94–97,123,124 ; growth and endocrinology ( n = 10, 10%) 78,98,99,125–131 ; caregivers and care burden ( n = 7, 7%) 10,37,40,79,80,100,132 ; other ( n = 2, 2%) 101,133 ; and musculoskeletal ( n = 1, 1%) 134 . Most studies ( n = 54, 53%) were retrospective cohorts or case series (Supporting Information: eFigure ), with a median sample size of 48 patients (range 20–240).…”
Section: Resultsmentioning
confidence: 99%
“…In the clinical (but also the home) setting, actigraphy offers the potential to provide evidence of such influences by comparing the acquired data with symptom records from care providers, e.g., through the so-called 24-h sleep protocol. This may also increase the overall understanding and knowledge of how various symptoms interact with sleep in this complex sample and whether, in turn, there may be “typical” associations with, for instance, medication administration or dosing [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, as our results may indicate, the current representation of the sleep patterns in PCM was not sufficient for the setting of PPC to the participants. As sleep disorders are highly prevalent in the context of PPC, a view to assess the progression of changes over 24 h should be added as a further improvement of the PMC [54,55]. Additionally, regarding the documentation of symptoms, numerous participant requests were identified that could lead to an improvement of the documentation.…”
Section: Discussionmentioning
confidence: 99%